Supply Chain Optimization approaches and Market Demand Analysis of Petroleum Industry: A Case Study of ONGC - Kumar Jha, Chandan (International Journal of Scientific Research and Management (IJSRM), 2016)
Problem discussion: Supply chain management plays very important role in petroleum industry to solve many problems like long lead time, transportation problem, operational management issue, supplier selection problem and service satisfaction at the different level. In this thesis the main focus is on finding options for optimization of the supply chain management in petroleum industries.Purpose: To study supply chain management in the petroleum industry and finding options for optimizing the supply chain in the petroleum industry by literature review and investigate previous literatures.Method: In this thesis ONGC Limited (headquartered in Dehradun, India) is taken consider for the case study. Qualitative research technique is implemented in this research. Primary data is collected via cell phone by communicating with organization’s employee and secondary data is taken from various research articles and books to make the theoretical frame of reference for the thesis.Scope of the study: The scope of this thesis is limited to the supply chain management optimization in the petroleum industry.Conclusion: Supply chain management Optimization is recognized as the main tool for the petroleum industries to achieve aggressive success in global competitive market. Analyzing ONGC Limited gives a realistic approach that how to optimize and manage its supply chain efficiently and effectively. The planning process, Information technology, marketing management and integrated operation management are the main strength of supply chain optimization